2021
DOI: 10.1186/s13020-021-00546-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis-dependent antidepressant-like activity of Hericium erinaceus in an animal model of depression

Abstract: Background Depression is a severe neuropsychiatric disorder that affects more than 264 million people worldwide. The efficacy of conventional antidepressants are barely adequate and many have side effects. Hericium erinaceus (HE) is a medicinal mushroom that has been reported to have therapeutic potential for treating depression. Methods Animals subjected to chronic restraint stress were given 4 weeks HE treatment. Animals were then screened for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 116 publications
(123 reference statements)
0
22
0
4
Order By: Relevance
“…The culinary-medicinal mushroom Hericium erinaceus, also known as the lion's mane mushroom, is well known for its diverse therapeutic activities related to neuroprotection [127,[157][158][159][160] and neuroregeneration [161][162][163] attributed to its antioxidant properties [127,160,164]. In a study by Lew et al [127], a standardized aqueous extract of H. erinaceus has been shown to possess higher total phenolic content and more potent reducing power compared to solvent extracts.…”
Section: Hericium Erinaceusmentioning
confidence: 99%
“…The culinary-medicinal mushroom Hericium erinaceus, also known as the lion's mane mushroom, is well known for its diverse therapeutic activities related to neuroprotection [127,[157][158][159][160] and neuroregeneration [161][162][163] attributed to its antioxidant properties [127,160,164]. In a study by Lew et al [127], a standardized aqueous extract of H. erinaceus has been shown to possess higher total phenolic content and more potent reducing power compared to solvent extracts.…”
Section: Hericium Erinaceusmentioning
confidence: 99%
“…Currently, the biggest challenge associated with psychedelic pharmacology studies is prohibition where psychedelics are classed as a Schedule 1 drug and the social stigma associated with their use. Chong et al, 2021 implied a predictive analysis method to investigate the molecular mechanisms of H. erinaceus [ 124 ], perhaps this offers a novel means of determining efficacy prior to clinical trials in line with prohibition. Other methods including ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis to investigate fungal biologics may also be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vivo studies on depressed animals demonstrated that when fed with H. erinaceus levels of the monoamine’s serotonin, dopamine and NE were elevated [ 123 ]. In vivo studies report that erinacine can increase monamine expression and modulate anti-inflammatory brain-derived neurotrophic factor (BDNF) signalling in depressed animals [ 124 ]. Amycenone, a proprietary mixture of compounds which are present in the fruiting body of H. erinaceus , demonstrated anti-inflammatory activity against cytokines TNF and IL and reduced inflammatory induced depression in test animals [ 119 ] a similar activity observed with SSRIs and SNRIs.…”
Section: Fungal Biologics: Unlocking the Potential Of Eastern Practic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hericium erinaceus (HE), also known as the monkey’s head mushroom, lion’s mane mushroom, or Yamabushitake, is commonly found in East Asia [ 18 ] ( Figure 1 ). It is well-known for its diverse therapeutic activities, including neuroprotection [ 16 , 17 , 19 , 20 ] and neuroregeneration [ 21 , 22 , 23 , 24 ], which are attributed to its neurogenesis, antioxidative, and anti-neuroinflammatory functions [ 17 , 19 , 20 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%